DEVELOPMENT OF INTERACTIVE MULTIMEDIA ENGLISH TO TEACH SPEAKING STUDENTS GRADE IX SMPN 02 TUREN - Lu’luatul Ilmiah; Siti Rofi’ah; Widiarini Widiarini (UIBU, 2023)
The purpose of this study is to teach English speaking, especially in the pronunciation of English words for grade IX students of SMPN 02 Turen. The method used in this study is Research & Development (R & D), which is a research method that focuses on the discovery or creation of new products. The results showed that students' lack of interest in the learning process was caused by a boring and uninteresting approach to teacher learning. Researchers use Interactive Multimedia to improve the teaching and learning process in the classroom because it is considered suitable and in accordance with existing problems. The product produced in this study is in the form of PPT videos that divide media quality into components of content, media, and interactivity